Smṛtigandha - Ārakaḍe, Madhukara (Ḍimpala Pablikeśana, 2016)
Autobiographical memoirs of Madhukara Ārakaḍe, 1952-2015, Marathi poet
In Marathi
Keywords: Autobiografie; Ārakaḍe; Madhukara 1952-2015; Poets; Marathi